2019
DOI: 10.1074/jbc.ra119.008000
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of aggregation and fibril formation of the amyloidogenic N-terminal fragment of apolipoprotein A-I

Abstract: The N-terminal (1-83) fragment of the major constituent of plasma high-density lipoprotein, apolipoprotein A-I (apoA-I), strongly tends to form amyloid fibrils, leading to systemic amyloidosis. Here, using a series of deletion variants, we examined the roles of two major amyloidogenic segments (residues 14-22 and 50-58) in the aggregation and fibril formation of an amyloidogenic G26R variant of the apoA-I 1-83 fragment (apoA-I 1-83/G26R). Thioflavin T fluorescence assays and atomic force microscopy revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(46 citation statements)
references
References 55 publications
5
41
0
Order By: Relevance
“…6A) and AFM images (Fig. 6B), the Δ32–40 and Δ50–58 variants form straight fibrils with transition to β‐sheet structure similarly to intact apoA‐I 1–83/G26R, whereas the Δ14–22 variant does not form apparent fibrils but rather form small spherical aggregates without secondary structural transition [38]. Dot blotting analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6A) and AFM images (Fig. 6B), the Δ32–40 and Δ50–58 variants form straight fibrils with transition to β‐sheet structure similarly to intact apoA‐I 1–83/G26R, whereas the Δ14–22 variant does not form apparent fibrils but rather form small spherical aggregates without secondary structural transition [38]. Dot blotting analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the first reported amyloidogenic variant, Iowa (G26R) [33,34], greatly enhances formation of amyloid fibrils by the 1–83 fragment of apoA‐I with a conformational transition from random coil to β‐strand‐rich structure [22,35]. Interestingly, the two highly amyloidogenic segments (residues 14–22 and 50–58) in the N‐terminal 1–83 fragment [36–38] overlap with the amphipathic α‐helix‐forming regions of apoA‐I upon binding to lipid [12,16,35].…”
Section: Introductionmentioning
confidence: 99%
“…Using circular dichroism, they also showed that the fragment 14-22 allows β-transition and fibrilization [216]. Studies with electron paramagnetic resonance spectroscopy [219], X-ray crystallographic studies [220] and hydrogen-deuterium exchange mass spectroscopy [221] showed that the G26R mutation induces helix destabilization of the protein in the N-terminal domain leading to a transition of residues 14-58 to a β-sheet conformation (Figure 7) [216]. In mature amyloid fibrils, ApoA1 N-terminal fragments are assembled in a parallel, in-register β-sheet structure and the protofilaments of ApoA1 present a β-strand-loop-β-strand structure [205,217].…”
Section: Apolipoprotein A1 (Apoa1)mentioning
confidence: 99%
“…Hereditary ApoA-I amyloidosis is characterized by deposition of the N-terminal 80-100-residue fragments as amyloid fibrils in peripheral organs. Mutation seems to perturb the native protein structure, making it more susceptible to proteolysis and thereby to the release of the N-terminal amyloidogenic fragment [216,217].…”
Section: Apolipoprotein A1 (Apoa1)mentioning
confidence: 99%
See 1 more Smart Citation